ON THE ISSUESTHE STUDY OF THE FUNCTIONAL CONTENT OF PHRASEOLOGICAL UNITS WITH THE COMPONENTS “HAND“ – “ҚЎЛ” IN THE CONTEMPORARY GERMAN AND UZBEK LANGUAGES. (Scientific journal of the Fergana State University, 2023)
The given article considers PU with the components “Hand“ – “қўл” through the examples in german and uzbek languages. The functional content of the PU hes been also taken into account in the analyses.